Hotelling's exhaustible resource extraction model as a linear program - John M. Hartwick (Queen's University, Department of Economics, 2023)
We "translate" Hotelling's continuous-time, exhaustible resource extraction Model of 1931 into a linear program of present value extraction cost minimization subject to a stock endowment and period by period demand constraints. The appropriate form of the demand constraints allows for resource rent rising at the rate of interest in the dual program. A useful variant has the stock size endogenous.
Keywords: Q320; C61; D46; 330; resource extraction; linear program; rent and interest rate